Plan de negocio: diseño de red de campesinado como alianza estratégica para la exportación de pitahaya y granadilla a Europa (2020)
In the present project, research is carried out to analyze the market, negotiation relations and possible opportunities in the export market. This project seeks the generation of jobs, sustainable development in rural areas, growth and development of the agricultural sectors, preservation of the countryside and the environment. During the development of the project, the opportunities for fruit exports to the European continent through alliances between farmers are investigated.